Project-Based Instruction Guided Lesson Study Improve The Achievement of Learning Outcomes on Educational Research Methodology Course at Department of Biology - Hadi Suwono (Bandar Lampung University (UBL), 2013)
The research of impact project-based instruction guided lesson study in Educational Research Methodology course has been conducted in 2010 until 2012. The research was focused to improve student achievement of learning outcomes in Educational Research Methodology course at Department of Biology, State University of Malang. The learning outcome was defined on three skill levels, understanding of educational research basic concept, creating of research proposal, and final grade. The research approach was classroom action research guided lesson study. The data is analyzed by comparing student score with the minimum requirement score and the improvement of score from cycle 1 to cycle 2 and cycle 3. The mean score of understanding research basic concept increase from cycle 1 to cycle 3. The implementation of project-based instruction guided lesson study improved the ability of students to create research proposal. The percentage of studentswho gotthe final gradeof A andA- increased from priorresearchtocycle1, cycle 2and cycle 3. On the contrary, percentageof studentswho have final gradeC, D,andEwere reduced. The study showed that project-based instruction guided lesson study improved the ability of students to achieve learning outcomes, comprehend research basic concept, creating research proposal, and higher final grade